Reading Romans as lament: Paul's use of Old Testament lament in his most famous letter - Crisler, Channing L. (Pickwick Publications, 2016)
Chapter 1: The Literary Form and Theological Message of Old Testament Lament -- Chapter 2: The Gospel as the Answer to the Righteous Lamenter (Romans 1:16-17) -- Chapter 3: The Gospel as the Answer to the Unrighteous Lamenter (Romans 3:1-26) -- Chapter 4: The Gospel as the Answer to the Lamenting “I” (Romans 7:7-8:4) -- Chapter 5: The Gospel as Answer to Groans and Inexplicable Rejection (Romans 8:18-39) -- Chapter 6: The Gospel as the Answer to Israel’s Intercessory Lamenter (Romans 9:1-11:36) -- Chapter 7: The Gospel as the Answer to the Church's Lament (Romans 15:1-6) -- Chapter 8: Lament and Paul's Theology of Suffering in Romans